2019
DOI: 10.1088/1755-1315/301/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion conditions on the physical properties of coconut rice-based extrudates

Abstract: Coconut meal is a by-product of coconut oil and coconut milk production. It is a rich source of dietary fiber which shows to have an important role in lowing the risk of various chronic diseases. Therefore, it is interesting to convert the coconut meal, previously recognized as a valueless by-product, into a nutritious food product. The aim of this work is to investigate the possibility of such conversion using a widely known extrusion method. The effect of extrusion variables, including the coconut meal conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…This finding is in agreement with those of Wang et al (2017), who explained that adding cherry pomace significantly decreased the WAI of snacks due to competition for water absorption between the pomace and starch. Earlier, Dumchaiyapoom et al (2019) found that WAI decreased with increased coconut meal in mixed rice and glutinous rice-based extrudates. Furthermore, it can be observed that the interaction had a significant (p ≤ 0.001) effect on the WAI.…”
Section: Water Absorption Indexmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding is in agreement with those of Wang et al (2017), who explained that adding cherry pomace significantly decreased the WAI of snacks due to competition for water absorption between the pomace and starch. Earlier, Dumchaiyapoom et al (2019) found that WAI decreased with increased coconut meal in mixed rice and glutinous rice-based extrudates. Furthermore, it can be observed that the interaction had a significant (p ≤ 0.001) effect on the WAI.…”
Section: Water Absorption Indexmentioning
confidence: 87%
“…Several by-products, such as pomace (Alam et al, 2016) and bagasse from fruits and vegetables (Navarro Cortez et al, 2016), bran, coat, and wasted grains from cereals (Fleischman et al, 2016;Unsaeng et al, 2019;Zhong et al, 2021), have been used in extruded snack applications. However, there have been only a few studies examining the use of coconut meal in extruded snacks (Khan et al, 2015;Dumchaiyapoom et al, 2019).…”
mentioning
confidence: 99%
“…Rasio Ekspansi (ER) Pengukuran dilakukan dengan membandingkan diameter ekstrudat dengan diameter die (Dumchaiyapoom et al, 2019). Diameter ekstrudat diukur menggunakan kaliper.…”
Section: Pengukuran Karakteristik Fisikunclassified